2013
DOI: 10.1007/s40261-013-0101-1
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Dexmedetomidine in Critically Ill Patients

Abstract: Background and ObjectivesAlthough the pharmacokinetics of dexmedetomidine in healthy volunteers have been studied, there are limited data about the pharmacokinetics of long-term administration of dexmedetomidine in critically ill patients.MethodsThis population pharmacokinetic analysis was performed to quantify the pharmacokinetics of dexmedetomidine in critically ill patients following infusions up to 14 days in duration. The data consisted of three phase III studies (527 patients with sparse blood sampling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 28 publications
3
36
1
2
Order By: Relevance
“…Dyck et al built a pharmacokinetic model of DEX which included height as a covariate for central clearance in non -obese (mean body weight of 82 kg) adult volunteers 10) . Valitalo et al 11) performed a population pharmacokinetic analysis of DEX in critically ill patients in the intensive care unit (ICU) and found that TBW strongly correlates to clearance, and their final model included a TBW covariate on clearance. Because the formula structure that they used was based on the allometric scaling technique which is frequently used for pharmacokinetic analysis of anesthetics in obese patients 12) , the increase in clearance with body weight was at an exponential rate.…”
Section: Discussionmentioning
confidence: 99%
“…Dyck et al built a pharmacokinetic model of DEX which included height as a covariate for central clearance in non -obese (mean body weight of 82 kg) adult volunteers 10) . Valitalo et al 11) performed a population pharmacokinetic analysis of DEX in critically ill patients in the intensive care unit (ICU) and found that TBW strongly correlates to clearance, and their final model included a TBW covariate on clearance. Because the formula structure that they used was based on the allometric scaling technique which is frequently used for pharmacokinetic analysis of anesthetics in obese patients 12) , the increase in clearance with body weight was at an exponential rate.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 confirms this, as only in the highest concentrations (sparse data), the precision decreases and bias increases. Figure 5 shows the population predictions versus time and observed concentrations for previously published dexmedetomidine pharmacokinetic models, 4,[6][7][8][9][10] showing poorer fits for all models compared with our final model. Also, as seen in the C obs /C pred versus time graphs in figures 3 and 5, our model predicts initial concentrations more accurately than the existing models, indicating that the accuracy concerning front-end kinetics is acceptable.…”
Section: Dexmedetomidine Pharmacokinetics In Volunteersmentioning
confidence: 98%
“…Most of the existing pharmacokinetic models for dexmedetomidine were obtained from trials involving postoperative and/or ICU patients, using either computer-controlled infusion with an unpublished model 7 or continuous infusion. [8][9][10] This approach is sensitive to the influence of confounding drugs such as subtherapeutic levels of anesthetic drugs, additional sedation or analgesia, and other medications. The resulting pharmacokinetic models are thus less applicable to single drug pharmacokinetic modeling.…”
mentioning
confidence: 99%
“…Intravenous dexmedetomidine 0.2-1.4 lg/kg/h demonstrated linear pharmacokinetics [4,31], and no accumulation was seen when dexmedetomidine was infused for up to 14 days [4]. Dexmedetomidine pharmacokinetics were adequately described by a two-compartment disposition model [4,20,32].…”
Section: Pharmacokinetic Profilementioning
confidence: 99%
“…The pharmacokinetics of dexmedetomidine were not altered to a clinically relevant extent based on age or gender or in patients with severe renal impairment [4,33], and no dosage adjustment is needed in the elderly or in patients with renal impairment [4]. Population pharmacokinetic analysis suggested a strong correlation between bodyweight and the clearance of dexmedetomidine [31]. Race did not appear to affect the pharmacokinetics of dexmedetomidine, with no significant differences seen between Caucasian and South Korean or Japanese subjects [7,34].…”
Section: Pharmacokinetic Profilementioning
confidence: 99%